2012
DOI: 10.1007/s00228-012-1396-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approaches to indirectly compare bioequivalence between generics: a comparison of methodologies employing artemether/lumefantrine 20/120 mg tablets as prequalified by WHO

Abstract: From a clinical viewpoint, not only are these prequalified generics bioequivalent and interchangeable with the reference product (Coartem, Novartis), but also the existing indirect evidence makes it possible to conclude that these WHO prequalified products are bioequivalent between themselves with respect to the AUC. The lack of the necessary precision to demonstrate bioequivalence between generics with respect to the C(max) within the conventional acceptance range does not preclude considering them as interch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…The authors concluded that even with the Bworse^scenario of 9.5 % non-bioequivalent products, this low value provides reassurance of the BE of two generic products that have been shown to be bioequivalent to the same reference product. However, this does not seem to be the worst scenario, but a very favorable one, because point estimate differences between generics can be larger [5,16]. Karalis et al (2013) plotted the probability of accepting BE between generics as a function of their point estimates and concluded that although two generics are bioequivalent to the reference product, this does not ensure that they are bioequivalent to one another [8].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors concluded that even with the Bworse^scenario of 9.5 % non-bioequivalent products, this low value provides reassurance of the BE of two generic products that have been shown to be bioequivalent to the same reference product. However, this does not seem to be the worst scenario, but a very favorable one, because point estimate differences between generics can be larger [5,16]. Karalis et al (2013) plotted the probability of accepting BE between generics as a function of their point estimates and concluded that although two generics are bioequivalent to the reference product, this does not ensure that they are bioequivalent to one another [8].…”
Section: Discussionmentioning
confidence: 95%
“…The 90 % CI for the indirect treatment comparisons for each computed scenario was calculated as described previously [5], and brief description of the method is provided as online resource 1.…”
Section: Statistical Analysis Of Indirect Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Gwaza et al , we selected the data from three bioavailability/bioequivalence studies conducted independently, which are available in WHO public assessment reports at https://extranet.who.int/prequal/ (https://extranet.who.int/prequal/sites/default/files/documents/MA052part6v1.pdf, https://extranet.who.int/prequal/sites/default/files/documents/MA062part6v1.pdf, and https://extranet.who.int/prequal/sites/default/files/documents/MA064part6v2.pdf). The studies compared fixed dose combination artemether/ lumefantrine 20/120mg tablets in adult healthy volunteers with the same brand name drug submitted to the WHO Prequalification of Medicines Programme.…”
Section: Real Example Analysismentioning
confidence: 99%
“…Furthermore, these differences could be larger for individual patients. There are, however, a number of mathematical models, which claim to address the potential interchangeability between different generic formulations through indirect comparisons 19 20. In one such analysis, Herranz and colleagues (2013) concluded that generic products were not only bioequivalent with the reference product but also with each other; however, the 80%–125% limits used in these analyses are now considered inappropriate for NTI drugs 21…”
Section: Bioequivalence and Interchangeabilitymentioning
confidence: 99%